Fiscal Policy Instruments and Human Development Index: Efforts to Improve the Welfare for Indonesian - Alek Surya Nugraha; Firmansyah, Muhamad Ferdy; Muhammad Ihsaan Rizqulloh; Yudha Hadian Nur (Langgas: Jurnal Studi Pembangunan, 2024)
The welfare of the community is something that a country needs to achieve. The economy and social life reflect the welfare of the community. To improve people's welfare, the Government needs to optimize a series of fiscal policy instruments to achieve this goal. This study seeks to see the effect of fiscal policy instruments in the expenditure sector to improve people's welfare with the HDI as a measure of community welfare. Using the quantitative descriptive method, the researcher attempts to see the effect of housing and community amenities, health, and education expenditure on the Indonesian HDI in 2010-2021. Using multiple linear regression analysis, it is found that 2010-2021, Housing and Community Amenities Expenditure, Health Expenditure, and Education Expenditure had a positive and significant impact on the Indonesian HDI. Researcher recommends the Government to increase the budget allocation for the three sectors.